2012
DOI: 10.2174/138920112802273227
|View full text |Cite
|
Sign up to set email alerts
|

Antivenoms for Snakebite: Design, Function, and Controversies

Eric J. Lavonas

Abstract: This article reviews the current state of the art for antivenom production and development. Particular attention is paid to controversies and trade-offs used to achieve a balance between improved safety and pharmacokinetic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Conversely, simplifying the cocktail composition may compromise its efficacy due to the high diversity of toxins comprising venoms. Furthermore, it is difficult to reconcile moves towards cocktail simplification with a major trend in antivenom formulation, namely to widen the spectrum of snake venoms covered by a single treatment (Lavonas, ; Stock et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, simplifying the cocktail composition may compromise its efficacy due to the high diversity of toxins comprising venoms. Furthermore, it is difficult to reconcile moves towards cocktail simplification with a major trend in antivenom formulation, namely to widen the spectrum of snake venoms covered by a single treatment (Lavonas, ; Stock et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ig precipitation methods with (NH4)2SO4 or caprylic acid yield products that are greater than 90% IgG but do not separate neutralizing IgG from non-therapeutically effective Ig molecules. However, this may be suitable for clinical use; the development of inexpensive IgG antivenoms with caprylic acid has been advocated for use in the developing world, where the high cost of antivenoms limits their use and leaves many victims without effective therapy (Lavonas, 2012) . Another exciting aspect of adding caprylic acid is its antiviral action: the non-ionized form of caprylic acid is lipophilic.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the monoclonal immunoglobulins used to treat autoimmune diseases, cancer or sepsis, all snake antivenoms are polyclonal preparations, is due to the complexity of snake venoms (Lavonas, 2012) , and the same applies to spider venoms. Serum producers worldwide carry out processes that result in sera containing IgG, Fab or even F(ab')2.…”
Section: Salox Contains Heterologous (Equine) Neutralizing Antibodies...mentioning
confidence: 99%
“…The dose for adults and children is the same. However, its use is still controversial11 and major adverse side effects of antivenom are related to its immunogenic potential and may include severe systemic reactions, anaphylaxis and serum sickness 12. There is emerging literature showing that antivenom appears to be safe in a paediatric population;13 a recent randomised controlled trial from Sri Lanka14 investigated the use of adrenaline, promethiazine and hydrocortisone prior to the administration of antivenom and suggested that low dose of subcutaneous adrenaline was the only treatment to exhibit an effect in reducing reaction rate to antivenom and that using hydrocortisone alongside the adrenaline negated this effect.…”
Section: Discussionmentioning
confidence: 99%